ENHANCING ECONOMIC COMPETITIVENESS THROUGH INNOVATIVE MARKETING STRATEGIES - Eka budi Yulianti; Sri Sugiarti; Shofia Asry (CV. ADIBA AISHA AMIRA, 2025)
Increasing economic competitiveness is a major challenge for companies and countries in the face of increasingly fierce global competition. One effective approach to achieve this goal is to implement innovative marketing strategies. These strategies include the use of digital technology, data analysis, product personalisation, and the development of creativity in promotion. Through innovative marketing, companies are not only able to fulfil customer needs more effectively but also create differentiation in a competitive market. With continuous innovation, companies can strengthen brand positioning, optimise interactions with customers, and open up opportunities for stable economic growth. Therefore, creative and tactical marketing strategies are key to improving economic competitiveness in the era of globalisation.